Populasi Kutu Kebul (Bemisia sp.) dan Gejala Penyakit Virus pada Berbagai Varietas Kentang di Desa Sembalun - Andalisa, Rani; Sarjan, Muhammad; Stella Petrunella Thei, Ruth (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aimed to determine the presence of whitefly pests (Bemisia sp.) and the symptoms of virus diseases caused by them on several potato varieties in Sembalun Village. The research was conducted from April to June 2021 in Sembalun Timba Gading Village, Sembalun District, East Lombok Regency, West Nusa Tenggara Province. The study used an experimental design with four potato varieties: Mc. Russet (A), Ranger Russet (B), Chitra (C), and Atlantik (D). Each treatment was replicated six times, resulting in a total of 24 experimental units. The results showed that the Mc. Russet and Ranger Russet varieties were more resistant to Bemisia sp. infestations in terms of both population and attack intensity. Whitefly populations fluctuated during the observation period, with the highest recorded at 49 days after planting (DAP) on the Chitra variety (2.08 insects/plant), and the lowest on Mc. Russet (1.33 insects/plant). The highest pest attack intensity was also observed at 49 DAP on the Chitra variety (1.0%), while the lowest was on Mc. Russet (0.4%). The highest incidence of yellow virus disease, transmitted by whiteflies, was recorded at 59 DAP on the Chitra variety (4.2%), and the lowest on the Ranger Russet variety (1.6%).